Marine Fishes of the Azores annotated checklist and bibliography : A Catalogue of the Azorean Marine Ichthyodiversity - Santos, Ricardo S. (2017)
The publication of the present work was funded by the Junta Nacional de Investigação Científica e Tecnológica (JNICT)- Lisboa. The research was made possible through grants received from Secretaria Regional da Agricultura e Pescas-Horta (Açores), INVOTAN- Lisboa, Fundação Calouste Gulbenkian- Lisboa, Fundação Luso-Americana para o Desenvolvimento- Lisboa. The work was developed at the Departamento de Oceanografia e Pescas of the Universidade dos Açores.